Molecular Characterization of Echinococcus granulosus sensu lato from Humans in Slovenia - Barbara Šoba; Špela Gašperšič; Darja Keše; Tadeja Kotar (Pathogens, 2020)
The larval form of tapeworms of the Echinococcus granulosus sensu lato species cluster cause an important zoonotic infection, cystic echinococcosis (CE). Molecular characterization of the cluster’s isolates from different hosts greatly contributes to a better understanding of its transmission dynamics. To date, no genetic information is available on CE in Slovenia. In this work, we characterized isolates from human CE cases. Parasite samples from 18 patients were collected, together with the patients’ demographic and clinical data. Genomic DNA was analyzed by conventional PCR and sequencing at four mitochondrial loci (cytochrome c oxidase subunit 1, cox1; NADH dehydrogenase subunit 1, nad1; NADH dehydrogenase subunit 5, nad5; and small ribosomal RNA, rrnS). Thirteen isolates were successfully amplified and sequenced. Seven (58.8%) patients were infected with E. granulosus sensu stricto (s.s.) G1, five (38.5%) with E. canadensis G7 and one (7.7%) with E. granulosus s.s. G3. Echinococcus canadensis G7, the pig genotype, was identified exclusively in autochthonous Slovenes, while the patients originating from the Western Balkans were all infected with E. granulosus s.s. Our findings suggest that pigs are important intermediate hosts for human CE in Slovenia.